Nucleotide diversity of a nuclear gene ITS region and chloroplast genes (matK, rbcL, rpoC1) of Canarium nigrum in some provinces in Northern Vietnam - Phong, Dinh Thi; Lieu, Tran Thi; Thu Hien, Vu Thi; Loc, Hoang Thanh (Vietnam Journal of Biotechnology, 2018)
In this study, three chloroplast genes (matK, rbcL and rpoC1) and one nuclear gene (ITS) were used to assess the nucleotide diversity for nine individuals of Canarium nigrum species in Bac Giang, Hoa Binh and Phu Tho provinces (three individuals from each province). The nucleotide sequence of the four regions (ITS, matK, rbcL and rpoC1) of C. nigrum were determined with the results showing their size to be 696 bp, 798 bp, 702 bp and 522 bp, respectively. Results of nucleotide sequence comparison for the studied samples exhibited 100% similarity for all the four gene regions. Sequence comparison with other species in the Canarium genus available in the GenBank revealed that the nucleotide diversity level (π) was the highest for the ITS gene (0.02), followed by matK (0.007), and the lowest for rbcL (0.003). The phylogenetic tree of C. nigrum with the species in Canarium genus indicated that the separation of species was the clearest for the rpoC1 gene, followed by rbcL, matK and ITS gene, with the bootrap values obtained from the branching nodes of each species ranging from 98 to 99%, 35 to 67%, 65 to 98% and 98 to 99%, respectively. The species C. nigrum had the closest nucleotide similarity to C. tramdenum (KP093200) and C. album (KP093198) for the ITS gene and to species C. subulatum (KR530509), C. acutifolium (KR530512) for matK gene region. These results suggests the rpoC1 gene region could be used as barcode for the species in genus Canarium.